Group Processes in the Circle of Security Program: A Preliminary Study. Issue 4 (December 2016) - Jonsdottir, Annika; Coyne, Joe
Abstract : This paper describes an exploratory study of one aspect of the Circle of Security (COS) attachment‐based parenting program: the group process used in its tape review sessions. During the tape review, a reviewing parent (RP) watches videos of interactions between themselves and their child, who is aged between one and six years. The RP watches these videos in the presence of facilitators and other parents (termed 'the observing parents (OP)') who are encouraged to comment on the videotaped behaviour of the RP and on the COS concepts captured on video. The comments of the OPs were assessed qualitatively by looking for themes and specific comments that gave insight into the experience of COS for the parents involved. The analysis indicates that the comments of the OPs are important to the change process of the COS program.